Blockbusta [compact disc] - Busta Rhymes (Musician) (Conglomerate Entertainment ; Epic Records, 2023)
Busta Rhymes returns with his 11th studio release, executive produced by Pharrell Williams, Timbaland, and Swizz, along with Busta himself. The new album contains lead singles Beach Ball featuring BIA; Luxury Lifestyle featuring Coi Leray; and OK featuring Young Thug.